Can a Digital Awareness Campaign Change Knowledge and Beliefs Regarding Cochlear Implants? A Study in Older Adults in 5 European Countries - Patrick S. C. D'Haese MBA; Vincent Van Rompaey MD, PhD; Marc De Bodt PhD; Paul Van de Heyning MD, PhD (SAGE Publishing, 2020)
There are 466 million people living with a disabling hearing loss and the challenges of managing this public health crisis cannot be underestimated. Yet, adult utilization of cochlear implants is poor with less than 10% of suitable candidates receiving one. The aim of this study was to investigate the awareness levels regarding cochlear implants in older adults after a digital campaign to raise awareness of cochlear implantation in this population. To address the lack of awareness of the cochlear implants in the general population, adverts were placed in online medical magazines and mainstream newspapers. Data were collected in 400 subjects via an online market research questionnaire, in Germany, Austria, Sweden, and the United Kingdom, and compared with baseline data collected in a previous study. Median click rates were in line with expectations for the medical industry and approximately 22 000 individuals clicked through to the cochlear implant Web site. However, there were few significant differences between the 2 sets of data. The Internet was consulted as much as the doctor for medical information in Germany, Austria, and Sweden. The study reinforces the importance of the Internet in accessing information about health, including hearing loss. The click through rates shows that there is interest in learning about cochlear implants. Further work is needed to assess the impact of this type of campaign on individuals who have already been identified as hearing impaired.